Negative Reactions to Positive Gender Stereotypes: Different Levels of Positivity Elicit Similar Negative Reactions. - Wang, Zhen; Zhao, Li; Zuo, Guoguo; Jetten, Jolanda; Guan, Jian (Archives of Sexual Behavior, 2025)
Positive stereotypes may elicit targets' negative reactions, but it is not well understood whether targets react differently to various levels of such stereotypes. Two studies examined targets' negative reactions to various levels of positive gender stereotypes. Chinese students were recruited as participants (N = 1204), who were randomly assigned to the somewhat, moderately, or extremely positive gender stereotype conditions or the control condition. Reactions to positive gender stereotypes were then measured. Results showed that both female and male participants who were exposed to positive gender stereotypes disliked the speaker stating such stereotypes more, experienced greater negative emotions, and perceived the speaker as more gender-prejudiced than those who were not exposed to such stereotypes. These negative reactions were more pronounced in female participants than in male participants. Furthermore, participants' negative reactions to different levels of positive gender stereotypes were similar, regardless of whether the stereotypes were somewhat, moderately, or extremely positive. These negative reactions elicited by positive gender stereotypes were mediated by both a sense of depersonalization and a sense of diminished autonomy. This research indicates positive gender stereotypes are like "sugar-coated bullets," appearing harmless ostensibly. However, even somewhat positive gender stereotypes may elicit targets' negative reactions, impairing interpersonal relations and perpetuating gender inequality under the radar.